MEDIA PENDIDIKAN: Peran dan Fungsinya dalam Pembelajaran - Umar, Umar (Institut Agama Islam Negeri (IAIN) Metro, 2014)
First of all media just known as aids in learning activities and the function is to give visual experience to students, increasing learning motivation, make it clear and esier the concept which complicated and abstract to be simple, concrete and easy for understanding. Now, learning media not only as an aids but also as a learning concept of technology that the function and used as a learning source inlearning proces.